Penerapan Konseling Kelompok dengan Teknik Direktif Terhadap Kejenuhan Belajar - Oktarina, Yunika; Suryati, Suryati; Marianti, Lena (Scidacplus, 2023)
This research is entitled Application of Group Counseling Using Directive Techniques Against Learning Burnout of Students at the Alharomain Semende Darat Laut Islamic Boarding School, Muara Enim Regency. This research aims to find out how the study boredom of students at the Alharomain Islamic Boarding School is described and how group counseling is applied to the learning boredom of Alharomain Islamic Boarding School students. The method used in this research is a qualitative research method. The subjects of this research were five students of class IV Ibtida'iyah Alharomain Islamic boarding school who felt boredom with learning. Data collection techniques in this research used interviews, observation and documentation. The data analysis technique in this research is data reduction, data presentation, and drawing conclusions. The results of the research show that there are several aspects to the description of boredom experienced by students, including emotional exhaustion due to excessive demands. The results of the application of group counseling services with directive techniques to the boredom of learning of Alharomain Islamic boarding school students by instilling self-confidence and providing motivation to create new things in the learning process so that changes in behavior occur in the students as desired.